Desain Aplikasi Pengelolaan Barang Berbasis Visual Basic 10 - Baharuddin, Herlinah (Patria Artha Technological Journal, 2022)
Today's business cannot be separated from technology, today's shops without technology cannot properly monitor the productivity of their companies. The Citra Warna Paint shop still uses a conventional system, which still uses paper as a medium for recording incoming goods and outgoing goods data. The research objective was to design an application interface for goods management information systems to facilitate staff in the process of managing goods. The test method used is the Black Box Method, the results of the execution are through testing and checking the functionality of the software. the design of the goods management information system is operated by processing goods data by inputting, editing, deleting and displaying reports (reports) based on the Visual Basic 10 application. Test results The interface-based goods management application system helps the admin in inputting incoming and outgoing goods data and managing and regulate the release and entry of goods.